Patents for the Physiological Quality in Seeds of Peach Rootstock Classified by Weight and Stored for Different Periods - Souza, Aline G.; Smiderle, Oscar J.; Menegatti, Renata D.; de Lima, Marcos Aurélio C.; das Neves, Tainá R.; Bianchi, Valmor J. (Recent Patents on Food, Nutrition & Agriculture, 2019)
Background: Among stone fruit, the peach (Prunus persica (L) Batsch) is one of the most widely grown species in Brazil, in both area cultivated and in production. Objective: The aim of this study was to evaluate the physiological quality of heavy and light seeds of four cultivars of Prunus persica for two storage periods, from tests of electrical conductivity, germination, and an analysis of initial plantlets growth. Methods: The Electrical Conductivity test (EC) was conducted in a Completely Randomised Design (CRD), in a 4 x 2 x 5 factorial scheme with five replications. The germination test was carried out in CRD, in a 4 x 2 factorial scheme with eight replications. The physiological quality of the seeds was determined at zero and twelve month’s storage. For the growth analysis, the experimental design was in CRD, in a 4 x 2 factorial scheme with four replications. Results: Under the conditions of the present study, it was found that the tests of germination and electrical conductivity were complementary in evaluating physiological quality in seeds of Prunus persica rootstock, suggesting that independent of the weight of the seeds, in ‘Capdeboscq’, ‘Aldrighi’, ‘Okinawa’ and ‘Okinawa Roxo’, there is a loss of quality and viability when the seeds are stored for a period of 12 months. Conclusion: Under the experimental conditions of the present study, it was concluded that storage for a period of 12 months in Recent patents is not rather recommendable for maintaining quality and viability in seeds of Prunus persica of the Capdeboscq, Aldrighi, Okinawa and Okinawa Roxo cultivars.
Keywords: viability